(untitled) (Research, Society and Development, 2022)
Coffee is one of the most consumed beverages in the world. As consumer habits have changed, new ways and techniques of preparation have come into use. In this context, cold brew has become common, which is a method of cold extraction where the coffee powder is in contact with water, usually for 12 to 48 hours. This work aimed to evaluate the influence of the preparation time and the impacts on the physical-chemical characteristics of cold brew. Organic coffee (Arabica typica) was used and different treatments related to the extraction time were adopted for infusion (12, 24, 36 and 48 h) at 18 °C, and for reference condition 5 min of infusion with water at 92 °C. Subsequently, the following analyses were performed: total soluble solids, extraction percentage, aqueous extract, reducing sugars, proteins, total titratable acidity, pH, caffeine, and total phenolics. The results of the analyses were submitted to analysis of variance, principal components and hierarchical grouping. It was noted that the time used in each condition was determinant to characterize the samples, because there was a significant increase in almost all physicochemical parameters evaluated. Thus, the samples extracted in 12 and 24 hours showed similar results, as well as the drinks prepared in 36 and 48 hours, therefore the best condition of infusion time for the preparation of cold brew beverage would be 24 hours, because it is observed that there was no excess in the extraction of components present in coffee.